A Model of Communication System with Vending Machines - Kostadinov , Aleksander; Hristov, Hristo (Research Highlights in Science and Technology Vol. 2, 2023)
The paper presents a model of a communication system between a vending machine, an end user and a service administrator. The designed model consists of a multimedia module, a control module and a communication module. The function of the multimedia module is to provide information about availability, prices, procedures for ordering products from the vending machine, etc. The system is managed by software that is installed on a server, a user device and a control unit. The communications used are made up of an infrastructure allowing two or more devices to exchange information two-way through the Internet. The designed model of the system is protected as a valid utility model under the number 2017003813U. Overall, the model purposes to progress user experience and operational competence of vending machines over and done with a well-designed communication system.